2021
DOI: 10.1080/00140139.2021.1958013
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder electromyography-based indicators to assess manifestation of muscle fatigue during laboratory-simulated manual handling task

Abstract: e Centre interdisciplinaire de recherche sur le cerveau et l'apprentissage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 74 publications
(128 reference statements)
2
7
1
Order By: Relevance
“…Activation levels were obtained from 9 Hz low-pass filtering of the full-wave rectified EMG signals normalized by the maximum voluntary muscle activation [24] obtained using the average of the maximum 2-sec non-consecutive window across all MVIC tests.…”
Section: ∑ 𝑇𝐹𝑅(𝑡) 𝑙𝑜𝑔 [𝑇𝐹𝑅 (𝑡)] 𝑛 𝑡=1mentioning
confidence: 99%
See 3 more Smart Citations
“…Activation levels were obtained from 9 Hz low-pass filtering of the full-wave rectified EMG signals normalized by the maximum voluntary muscle activation [24] obtained using the average of the maximum 2-sec non-consecutive window across all MVIC tests.…”
Section: ∑ 𝑇𝐹𝑅(𝑡) 𝑙𝑜𝑔 [𝑇𝐹𝑅 (𝑡)] 𝑛 𝑡=1mentioning
confidence: 99%
“…However, as stated by Rampichini et al, [28], future standardized fatiguing protocols are needed to confirm whether the largest Lyapunov exponent could be an To this end, an interesting approach is to predict the rate of perceived exertion (RPE), which is known to increase with muscle fatigue [61], from MMF indicators. Interestingly, several studies have also shown a close relationship between the RPE [62] and MMF indicators [24,[63][64][65][66][67][68]. For instance, Goubault et al, [24] used correlation analyses between six MMF indicators and RPE scores assessed using the CR-10 Borg scale [69] during a laboratory simulated manual handling task.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the occurrence of muscle fatigue, the time domain features of sEMG generally show an upward trend over time ( Goubault et al, 2022 ). RMS and iEMG not only reflect the amplitude changes of the sEMG signal in the time domain but also clearly reflect the biomechanical properties and muscle energy changes in the exercise process ( Silvetti et al, 2017 ; Wu et al, 2017 ).…”
Section: Time-domain Feature Analysismentioning
confidence: 99%